Studi Kelayakan Bisnis Usaha Batik Dengan Metode Finansial (Studi Kasus Batik New Collet Desa Jatipelem Kecamatan Diwek Kabupaten Jombang) - Siti Nur Qomariyah (Jurnal Studi Manajemen dan Bisnis, 2021)
The emergence of new technology (printing) that can change the way batik is made, make batik craftsmen experience a shift. This is a problem because of the difficulty in marketing batik as traditional clothing. In the midst of this difficulty, batik craftsmen must survive because with the assumption that batik is a cultural heritage. Therefore, it is necessary to conduct a feasibility analysis in order to avoid losses. This study aims to see the feasibility of batik business from the financial aspect. This research was conducted on Batik New Collet in Jati Pelem Village, Diwek District, Jombang Regency, with purposive sampling method as the method of selecting the research site. This research was conducted in March 2021 until it was completed. Data collection techniques in this study are primary data and secondary data. The results of research on Batik New Collet for the last five years are; NPV of Rp. 913,104,722, IRR of 14.07%, Net B/C of 1.80 and R/C of 4.07. Based on the results of the research, the Batik New Collet business can be said to be feasible.